Análisis financiero en galtor supermercado de la ciudad de Loja, periodo 2019-2020 y la incidencia de la pandemia covid 19 en los resultados económicos de la empresa - Jaramillo Calderón, Jennyffer Tatiana (2022)
The present degree work called: FINANCIAL ANALYSIS OF THE GALTOR SUPERMARKET OF THE CITY OF LOJA, PERIOD 2019-2020 AND THE INCIDENCE OF THE COVID-19 PANDEMIC ON THE ECOCOMICAL RESULTS OF THE COMPANY was developed with the purpose of obtaining a diagnosis on the state of the company, in a way that allows knowing the economic and financial position; In addition, to obtain the Degree of Bachelor of Accounting and Auditing, Public Accountant - Auditor. The general objective of the degree work is: To carry out the financial analysis in GALTOR SUPERMARKET of the City of Loja, Periods 2019-2020, through the application of financial indicators to determine the incidence of the Covid-19 pandemic in the economic results of the Company. For the development of the general objective, the respective specific objectives are presented: Carry out the vertical and horizontal analysis of the financial statements to determine their variations as a result of the Covid-19 pandemic. Apply financial indicators that allow knowing the liquidity, profitability, activity and indebtedness that the company has of the years investigated, with their respective interpretation. Prepare a financial analysis report that contains the conclusions and recommendations that allow making the right and timely decisions The elaboration of the work, both in its theoretical and practical part, is based on the application of different methods, starting from the scientific method that is the basis of theoretical-practical research; followed by the deductive and inductive method with which the information collected from the general to the particular was ordered; The statistical method was also used, which facilitated obtaining the data in a summarized way in tables and graphs, thus allowing a greater understanding of the results and finally the analytical and synthetic method used to interpret the results of the calculations and in this way be able to issue policies, conclusions and recommendations that allow the correct decisión making in the Company. At the end of this titling work, the final financial analysis report is presented, in which the respective comments, conclusions of the results and recommendations of the deficiencies found are presented, which will allow making correct and timely decisions, improving the development of the company and determine management strategies to improve the financial management of the entity